Impacts of non-residential solar on residential adoption decisions - O'Shaughnessy, Eric; Barbose, Galen; Grayson, Alexandra; Ferrall-Wolf, Isa; Sunter, Deborah (Frontiers in Sustainable Energy Policy, 2023)
Household decisions to adopt rooftop solar photovoltaics are partly driven by social influence. Previous research on solar adoption influence has focused on influence among residential peers. Here, we expand the framework of solar adoption influence by exploring the influence of nonresidential installations on residential adoption decisions. We use staggered differences-indifferences to estimate non-residential influence effects using a large data sample of residential adoptions. We also critically evaluate prevailing frameworks for solar adoption influence. We find that non-residential installations are associated with accelerated residential adoption rates, on the order of 0.4 additional residential adoptions per quarter per non-residential installation. We show that non-residential systems exert a continuous, long-term influence on residential adoption decisions. We explore separate results and influence mechanisms for solar installed on commercial buildings, government buildings, and houses of worship. The results suggest that non-residential solar adopters could serve as partners in policies to "seed" residential adoption in underserved communities.This is a provisional file, not the final typeset article Gillingham et al. 2022). The impacts of previous adoptions on subsequent adoption decisions are evident in the physical clustering of PV systems and statistical associations between the timing of PV installations and adoption decisions (Bollinger and Gillingham 2012).The relationship between past and subsequent PV adoptions has been characterized as a form of social influence (Axsen and Kurani 2012, Xiong, Payne et al. 2016, Baranzini, Carattini et al. 2017, Wolske, Gillingham et al. 2020). The term "influence" has been used in PV adoption research in a broad sense. Rooftop PV adoption decisions may be directly affected by active social interactions, such as with neighbors who have already adopted (Sigrin, Dietz et al. 2017). The literature also suggests a role for more passive influence mechanisms, such as an individual being primed to adopt PV after seeing panels installed on another home (